A synthesis of the work of CCAFS and partners on gender and social inclusion (GSI) and climate policy - Chaves, Paola; Thornton, Philip K.; Cramer, Laura K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Women and girls are disproportionately affected by global crises such as climate change and environmental degradation. Moreover, the key role of women in agriculture and in sustaining the livelihoods and food security of their households in low-income countries, emphasises the need to address the gender gap. Therefore, gender transformative research that informs policy makers and improves the design of innovative and equitable climate laws and policies and adaptation and mitigation strategies is needed. This document presents a synthesis of the work of CCAFS in integrating a gender perspective into climate change policies and agreements at global, national and subnational levels in the last ten years (2010-2020). A contribution analysis (CA) based on the Theory of Change (ToC) of the Gender and Social Inclusion (GSI) Strategy was carried out. We collected the evidence through deep dives in the Outcome Impact Case Reports (OICRs) and interviews with key stakeholders working in each region where CCAFS has developed activities related with gender and policies. Our preliminary results show that, by using a multilevel governance approach to policy processes, the CCAFS program has contributed to anticipated outcomes and that it has played a key role in raising awareness about GSI and gender-transformative approaches in agriculture and climate policy agenda. However, all the efforts have proved insufficient to achieve the transformation that women and girls throughout the world need to see in international and national debates, policies, and practices concerning climate crisis. Therefore, our suggestion is to involve civil organizations and invest more in strengthening institutions for gender-transformative societies.